2015
DOI: 10.18805/ijar.5538
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression of Th1 and Th2 cytokines in bovine peripheral blood mononuclear cells during early pregnancy

Abstract: Conceptus-derived signals are involved in the maternal systemic immune regulation through blood circulation and lymph circulation by peripheral blood mononuclear cells (PBMC) in cattle. There exists a Th2-biased response in maternal uterus during early pregnancy in cattle. However, it is unclear that the changes in expression of Th1 and Th2 cytokines in PBMC during early pregnancy in cows. At present study, the expression of Th1 and Th2 cytokines in PBMC were explored at day 18 non-pregnant cows, day 18 and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In a study of 1,105 dairy herds, Charlier et al (2007) reported a negative phenotypic association, at the herd-level, between antibody response to F. hepatica and calving interval. The fact that antibody responses to both F. hepatica and O. ostertagi were favorably genetically correlated with fertility traits in the present study supports the view that animals inclined towards a TH2-type cytokine immune response have a tendency to maintain pregnancy (Oliveira et al, 2013;Zhang et al, 2015;Yang et al, 2016).…”
Section: Genetic Correlations With Fertility Traitssupporting
confidence: 84%
“…In a study of 1,105 dairy herds, Charlier et al (2007) reported a negative phenotypic association, at the herd-level, between antibody response to F. hepatica and calving interval. The fact that antibody responses to both F. hepatica and O. ostertagi were favorably genetically correlated with fertility traits in the present study supports the view that animals inclined towards a TH2-type cytokine immune response have a tendency to maintain pregnancy (Oliveira et al, 2013;Zhang et al, 2015;Yang et al, 2016).…”
Section: Genetic Correlations With Fertility Traitssupporting
confidence: 84%
“…We also reported that there were changing expressions of Th1 and Th2 cytokines in bovine peripheral blood mononuclear cells (PBMC) during early pregnancy [34] . It is known that macrophages play a crucial role in initiating the immune response.…”
Section: Discussionmentioning
confidence: 98%
“…The spleen is an important site where IgA B-cells proliferate and differentiate because of the structure and location of this organ in systemic circulation; this organ is also complicated and regulated by cytokines and chemokines. Cytokines, such as interleukin-1 (IL-1) (Ben-Sasson et al, 2009), IL-2 (Bell et al, 2015;Yang et al, 2016), IL-6 (Ramsay et al, 1994;Zhong et al, 2019), IL-10, interferon- (IFN-) and tumour necrosis factor-α (TNF-α) (Reis et al, 2011;Dorhoi and Kaufmann, 2014), are factors necessary to develop IgA-producing B-cells. These B-cells either remove invading microorganisms by developing neutralising antibodies or eliminate viruses by activating cytotoxic T-cells (Joosten et al, 2013).…”
Section: Introductionmentioning
confidence: 99%